The strategy of economic development - Hirschman, Albert O. (New York : Norton, 1959)
This book deals with strategy of economic development, the need for build-in spurs and the maintenance problem and solution
Original ed. published by Yale University Press, New Haven.
Includes bibliographical references and indexes.
oo 28/9/18
Loans
Keywords: Economic development